City competitive space and office development : Kuala Lumpur / Hazwani Harun - Harun, Hazwani (2011)
With globalisation, cities are facing increasing competitions as centers for activities and nodes for multi-national corporations. Measuring city competitiveness is an attempt to estimate a city's relative economic strength and potential. But while cities do compete, their primary purpose is not to produce a marketable output nor to maximize the rate of return on assets. Indeed, cities do not have one output nor clear inputs. Nor can they be bankrupted or liquidated. As such, this research is been undertaken to explore the physical and economic development of Kuala Lumpur pertaining to the office development in order to achieve higher competitive city space. To achieve this aim, the study start by review and discuss the general linkage between the office development and competitive city space; investigate the roles and influences of office development with regards to economic and physical development in cities; analyse the behaviour of headquarters office in relation to the change of office location; examine the issues and problems of office development trend in Kuala Lumpur; and develop recommendations on office development in order to achieve competitive cities. To understand about this research, the literature review has been prepared which focuses on office development towards city competitiveness. This covers an overview of its impact on built environment, role of office development towards city competitiveness, factor influencing office location, activities of the institutions of city competitiveness and management on sustainable competitive advantage were discussed. The study reveals some of the experiences on the growth of city form in urban area in several countries. The study area is Kuala Lumpur, as the fastest growing metropolitan region in the country as well as rank at 26th position, out of 139 countries in Competitiveness Index. Kuala Lumpur is the capital and economic centre of Malaysia. The Kuala Lumpur office market is robust and is experiencing increasing demand for offices with the expansion of the services sector. With the market poised to improve in terms of rents and capital values, investment is strong with investor funds coming from other countries. These foreign funds seek to invest in offices while a few are even participating in office developments around Kuala Lumpur City through partnership with local developers. From the analysis, the impact of office development in competitive city: Kuala Lumpur, found that in term physical aspect, there are including impact on city planning, infrastructure, urban structure and accessibility. While, in the economy aspects the impact that are taken into account are congestion cost, other costs, capital and competition which overall are moderate. This shows that, the impact on city is unsatisfactory. Recommendations are according to which the area is “a dynamic world-class centre for business and innovation. Its high-quality services, creativity and adaptability promote the prosperity of its citizens and bring benefits to all of Kuala Lumpur and the peripheral cities. The urban area is being developed as a unified region close to nature where it is good to live, learns, work and do business”.